Quality Characteristics and Αlpha-Tocopherol Content of Shea Butter Samples from Selected Markets Within Three Southwestern States of Nigeria (Dhaka University Journal of Pharmaceutical Sciences, 2022)
Shea (Vitellaria paradoxa) butter samples from selected markets in Nigeria were analyzed for AOAC quality characteristics and α-tocopherol content. The α-tocopherol was determined by RP-HPLC and mg per serving and % daily values (% DV) were estimated. The ranges of acid value (AV) [mgKOH/kg], free fatty acid (FFA) [%], peroxide value (PV) [meqO2/Kg], iodine value (IV) [gI2/100g] and saponification value (SV) [mgKOH/g] were 2.20- 2.59, 1.15-1.30, 0.75-0.95, 44.43-47.85 and 170.08-259.30, respectively. The -tocopherol had a retention time of 3.561 minutes and its content ranged from 1.15-2.60 mg/100 g in the samples, but 5.25 mg/100 g for the laboratory sample. Milligram (mg) per serving and percentage dietary value were 0.16-0.74 and 1.07-4.93, respectively. Quality characteristics varied significantly (p < 0.05) both within and across different markets. Based on the PV and IV results, the marketed shea butter samples may be both food and industry-grade but failed the FFA test. Similarly, 40% of samples did not qualify for domestic consumption and food industry applications. Hence, the samples with